Arteria Lusoria: An Anomalous Finding during Right Transradial Coronary Intervention - David Allen; Hilary Bews; Minh Vo; Malek Kass; Davinder S. Jassal; Amir Ravandi (Case Reports in Cardiology)
Arteria Lusoria or aberrant right subclavian artery (ARSA) is present in 0.6–1.4% of individuals. It typically remains clinically silent and is often discovered during angiographic procedures. The presence of ARSA can make a right transradial approach for coronary angiography and angioplasty technically more difficult. With the use of catheter support, we describe two cases in which a right transradial approach for catheterization was successful in the setting of ARSA. As such, the presence of ARSA does not warrant abandoning a transradial approach for coronary angiography and angioplasty.